PENGARUH METODE PERSONAL SELLING DALAM PEMASARAN PAKET WISATA DI PT MITRA PERSADA TRAVELINDO YOGYAKARTA - , ARGO VILAR, Pitaya, S.E.T., M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The Travel Agent began to grow as a symptom of a release and fun travel or leisure travel, as a way to escape from the busyness of the world of work and boredom of life. At this time the need to travel tourism through a travel agency or tour and travel is increasing. Therefore, they invented a tour package to facilitate the tourists to travel. PT Mitra Persada Travelindo, local travel agents as retailers tour packages, tour packages in product sales PT Mitra Persada Travelindo this is getting a benefit, the amount of commission for every travel agency is the same in principle, but to overcome the competition between the travel agency to another. Therefore, they invented a tour package to facilitate the tourists to travel. PT Mitra Persada Travelindo, local travel agents as retailers tour packages, tour packages in product sales PT Mitra Persada Travelindo this is getting a benefit, the amount of commission for every travel agency is the same in principle, but to overcome the competition between the travel agency to another. This final report was made aiming to determine the extent of the influence of the marketing methods used by PT Mitra Persada Travelindo Personal Selling particular method, to determine the extent of the influence of personal selling method, the writer uses descriptive data analysis methods are intended to identify the weaknesses and advantages of personal selling method to sales PT Mitra Persada tour packages Travelindo, to the problems that arise in applying this method of personal selling. Based on data analysis, it can be seen that, personal selling method is very influential in the promotion and sale of tour packages in PT Mitra Persada Travelindo. It can be seen from the sales of tour packages of the year 2012-2013 has always experienced a significant increase.